Genetic Variation and Potential for Resistance Development to the tTA Overexpression Lethal System in Insects. Issue 4 (1st April 2020) - Knudsen, Katherine E; Reid, William R; Barbour, Traci M; Bowes, Laci M; Duncan, Juliana; Philpott, Elaina; Potter, Samantha; Scott, Maxwell J
Abstract: Release of insect pests carrying the dominant lethal tetracycline transactivator (tTA) overexpression system has been proposed as a means for population suppression. High levels of the tTA transcription factor are thought to be toxic due to either transcriptional squelching or interference with protein ubiquitination. Here we utilized the Drosophila melanogaster Genetic Reference Panel (DGRP) to examine the influence of genetic variation on the efficacy of a female-specific tTA overexpression system. The level of female lethality between DGRP lines varied from 11 to 97% with a broad sense heritability of 0.89. A genome-wide association analysis identified 192 allelic variants associated with high or low lethality ( P < 10 −5 ), although none were significant when corrected for multiple testing. 151 of the variants fell within 108 genes that were associated with several biological processes including transcription and protein ubiquitination. In four lines with high female lethality, tTA RNA levels were similar or higher than in the parental tTA overexpression strain. In two lines with low lethality, tTA levels were about two fold lower than in the parental strain. However, in two other lines with low lethality, tTA levels were similar or approximately 30% lower. RNAseq analysis identified genes that were up or downregulated in the four low female lethal lines compared to the four high lethal lines. For example, genes associated with RNA processing and rRNA maturation were significantly upregulated in low lethal lines. Our data suggest that standing genetic variation in an insect population could provide multiple mechanisms for resistance to the tTA overexpression system.